Causative Factor of Low Birth Weight (LBW) Babies in Bandung City Hospital - Nursilawati, Deva; Cahyaningsih, Henny; Dharmansyah, Dhika (Jurnal Pendidikan Keperawatan Indonesia, 2023)
The LBW mortality rate reaches 15 to 20% in the world. the proportion of infant deaths originating from the age of 0-28 days (Neonatal) was 84.63% or 3.32/1000 live births and and body weight 2500 grams reached 6.3%, while the proportion of babies born weighing 2500 grams with body length 48 cm in Indonesia reached 4.0% and in West Java reached 4.2%. The purpose of this study was to determine the factors that cause babies born with low birth weight. The type of research used by researchers is a descriptive survey research method using a retrospective study design using medical record register data for newborns who have been treated. The population in this study were all low-birth-weight babies in the last year at Bandung City Hospital, using secondary data at the medical record installation section in the last year as many as 543 babies. The sample in this study is secondary data from babies born with LBW as many as 85 respondents. The sampling technique is probability sampling using a random sampling method using register data from medical records. The analysis in this study uses univariate analysis to see the frequency distribution of each sub-variable. The results of the study occurred in multipara parity, namely 46 (54.1%), gestational age at risk, namely 47 (55.3%), maternal age at risk, namely 46 (54.1%), twin births, namely 19 (22.4%) of the 85 respondents, pregnancies without placenta previa were 77 (90.6%). The results of this study indicate that the factor of gestational age is the highest that causes LBW babies to be born. It is recommended that efforts be made to reduce the number of LBW babies born by optimizing preventive efforts, health workers are required to provide health education about the causes of LBW.